Management Funding Strategies and Administrative Effectiveness of Private Universities in Ogun State, Nigeria - Akinsuroju, Oluwatosin Emmanuel; Anyanwu, Oluwakemi M.; Akinwande, Benson Orimisan (NIU Journal of Humanities, 2019)
This paper examined the relationship between Management Funding Strategies and Administrative Effectiveness of Private Universities in Ogun State. The design adopted for the study was descriptive survey research design. The population of the study were all the fifty (50) principal officers in the 10 approved private universities in Ogun State Nigeria. All the 50(100%) principal officers (Vice-Chancellors, Deputy Vice-Chancellors, the Registrars, the Bursars and the Librarians) who were referred to as the management team of these universities participated in the study. As a result of this, no sampling was carried out. Questionnaire tagged â€œManagement Funding Strategies and Administrative Effectiveness Questionnaireâ€ (MFSAEQ) were used to collect data. Inferential statistics (Pearsonâ€™s Product Moment Correlation and Multiple Regression) were used to test the six hypotheses at 0.05 level of significance. Finding however indicated that income generated from tuition, income generated from Revenue Yielding Projects, Loan from Bank, and Income generated from Donation have significance relationship with Administrative Effectiveness (r = 0.105, P< 0.05), (r = 0.356, P< 0.05), (r = 0.369, P < 0.05), and (r = 0.302, P < 0.05) respectively. Findings also revealed that each of the independent variables covered in this study have individual effect on Administrative Effectiveness (R 2 = 0.16, P<0.05).  Findings finally shown that there is a joint or composite significant effect of independent variables on Administrative Effectiveness (F = 553.04, P< 0.05). Based on the above findings, some of the recommendations made include; Private universities should increase the gap between the revenue generated from the school fees and the running cost of the university. Private universities should tackle funding challenges by establishing more revenue yielding ventures instead of depending on the income generated from the tuition fees. Keywords: Management Funding Strategies, Administrative Effectiveness, Private Universities.